Demokrasi di Mata Anak Muda: Studi Representasi Sosial - Hartoko, Victorius Didik Suryo (Fakultas Psikologi Universitas Sanata Dharma, 2023)
How do young people understand democracy? This study tries to find out the ideas of young people about democracy and its basic structure using the Social Representation approach. Young people aged between 17 to 33 years (N = 237 people) participated in this study. Data collection was carried out using a survey technique by asking them what they thought about democracy and what values they saw as the basic values of democracy. The three main ideas of young people about democracy are freedom of opinion (63.98%), plurality and equality (62.03%) and justice (48.52%). These three ideas are basic values for the formation of assertive citizens and at the same time reflect the need for young people to be independent and participate. Multidimensional scaling statistical techniques are used to summarize and capture the basic structure of 13 ideas about democracy. There are two main dimensions found. The first dimension describes democracy as a tension between the ideas of liberal democracy (freedom of opinion and equality-plurality) and the idea of integralism (prosperity, unity, law and order, responsibility and honesty). The second dimension describes democracy as the tension between the principles of justice and the principles of people's sovereignty (people's sovereignty, deliberations, general elections and togetherness). These two dimensions may reflect the history of the democratic experience of the Indonesian people who have experienced various trials of applying different ideas about democracy.